Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) TTerhadap Kemampuan PemahamanKonsep Matematis Siswa Kelas X SMA Negeri 3 Binjai Tahun Pelajaran 2017/2018 - Faqih Hakim Hasibuan (Studi Multidisipliner: Jurnal Kajian Keislaman, 2018)
This study aims to determine the effect of using the Cooperative Think Pair Share (TPS) type on the ability to understand students' mathematical concepts. This research, which was conducted in the 2017/2018 Academic Year 3 Binjai High School, was a quasi-experimental study, with the design of the pretest and posttest control group design. Based on the results of the study, the average value of the experimental class pretest was 48.03 and the average value of the control class pretest was 46.33. While the average value of the experimental class post test is 54.78 and the average value of the control class posttest is 50.47. There is a significant effect between TPS type cooperative learning on the ability to understand students' mathematical concepts which can be seen from the results of simple linear regression test calculations obtained rtable = 0.329, while based on the calculations that have been done obtained r count = 0.71. From the calculation it can be seen that r count r table (0.71 0.329). Thus the proposed hypothesis is accepted.